1999
DOI: 10.1523/jneurosci.19-03-01142.1999
|View full text |Cite
|
Sign up to set email alerts
|

Different Contributions of the Hippocampus and Perirhinal Cortex to Recognition Memory

Abstract: Brain regions involved in visual recognition memory, including the hippocampus, have been investigated by measuring differential neuronal activation produced by novel and familiar pictures. Novel and familiar pictures were presented simultaneously, one to each eye, using a paired viewing procedure. Differential neuronal activation was determined using immunohistochemistry for the protein products of c-fos as an imaging technique. The results establish that the regions of the rat brain associated with discrimin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

47
384
2
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 408 publications
(434 citation statements)
references
References 47 publications
47
384
2
1
Order By: Relevance
“…Here, we found that the perirhinal cortex was bilaterally more engaged by object encoding compared to position encoding. This supports our hypothesis that the perirhinal cortex is involved in object-specific encoding; and the finding corroborates similar results from both the human and non-human primate literature (Aggleton and Brown, 2005;Wan et al, 1999;Bussey et al, 2002Bussey et al, , 2005. Converging evidence from lesion studies of monkeys (Baxter and Murray, 2001), rats (Prusky et al, 2004) and humans (Barense et al, 2005), as well as from neuroimaging studies (Pihlajamäki et al, 2005) have implicated the perirhinal cortex in object processing.…”
Section: Discussionsupporting
confidence: 90%
“…Here, we found that the perirhinal cortex was bilaterally more engaged by object encoding compared to position encoding. This supports our hypothesis that the perirhinal cortex is involved in object-specific encoding; and the finding corroborates similar results from both the human and non-human primate literature (Aggleton and Brown, 2005;Wan et al, 1999;Bussey et al, 2002Bussey et al, , 2005. Converging evidence from lesion studies of monkeys (Baxter and Murray, 2001), rats (Prusky et al, 2004) and humans (Barense et al, 2005), as well as from neuroimaging studies (Pihlajamäki et al, 2005) have implicated the perirhinal cortex in object processing.…”
Section: Discussionsupporting
confidence: 90%
“…Lesions of the perirhinal cortex result in impairments in recognition but not spatial tasks whereas lesions of the hippocampus result in impairments in spatial but recognition tasks (Ennaceur and Aggleton, 1994;Bussey et al, 2000;Abe et al, 2009). Similarly, electrophysiological (Zhu and Brown, 1995;Zhu et al, 1995a) and c-Fos studies (Zhu et al, 1996(Zhu et al, , 1997Wan et al, 1999;Jenkins et al, 2004;Amin et al, 2006) have shown that the perirhinal cortex is recruited more during recognition than spatial tasks and vice versa for the hippocampus. There is mounting evidence to suggest that the hippocampus may indeed play a role in recognition memory (Hammond et al, 2004;Prusky et al, 2004) but the overwhelming consensus is that the perirhinal cortex alone is sufficient for completing recognition memory tasks.…”
Section: Object Recognition Memorymentioning
confidence: 96%
“…Immediate early gene imaging studies have shown that the perirhinal cortex is activated following object recognition tasks (Wan et al, 1999;Aggleton and Brown, 2005;Warburton et al, 2005) and following the presentation of novel visual stimuli (Zhu et al, 1995b(Zhu et al, , 1996(Zhu et al, , 1997, thus indicating that the perirhinal cortex plays a central role in novelty detection. Lesions of the perirhinal cortex have been shown to impair performance in the object recognition task (Ennaceur et al, 1996;) and more recent work has shown that the perirhinal cortex is required for the encoding, consolidation and retrieval of object recognition memory (Winters and Bussey, 2005a,b;Winters et al, 2008).…”
Section: Object Recognition Memorymentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of c-fos is induced by a variety of stimuli (Smith et al 1992;Melia et al 1994;Duncan et al 1996) and after some forms of learning (McCabe and Horn 1994;Radulovic et al 1998;Wan et al 1999;Vann et al 2000). Accordingly, Fos expression is considered a mechanism by which brief stimuli can trigger long-term changes in gene expression and alter the structural and functional properties of nerve cells (Goelet et al 1986;Morgan and Curran 1991).…”
mentioning
confidence: 99%